1998
DOI: 10.1055/s-2007-978879
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperleptinemia Does Not Modify Insulin Sensitivityin vivoin the Rat

Abstract: Insulin resistance is associated with hyperleptinemia, whilst exposure of hepatoma cells and isolated adipocytes to high concentrations of leptin has been demonstrated to result in attenuated insulin response and a reduced suppression of gluconeogenesis. To determine the acute metabolic effects of hyperleptinemia, we measured whole body glucose uptake (WBU) and hepatic glucose production rate (HGP) in rats using the euglycemic hyperinsulinemic clamping technique. Anesthetised male rats received recombinant mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Additionally, circadian peaks of leptin are positively correlated with insulin resistance in humans (5), and leptin concentrations are higher in insulin-resistant than insulin-sensitive men, regardless of adiposity (53). In other studies, no effects of leptin on insulin sensitivity were observed (60,63).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, circadian peaks of leptin are positively correlated with insulin resistance in humans (5), and leptin concentrations are higher in insulin-resistant than insulin-sensitive men, regardless of adiposity (53). In other studies, no effects of leptin on insulin sensitivity were observed (60,63).…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz et al (234) calculated that 42% of leptin's hypoglycemic action was independent of weight reduction. In contrast, the effects of leptin on whole body glucose metabolism in nonobese, nondiabetic animals remain inconsistent, but in general, short-term administration of leptin does not affect glucose metabolism (100,227,275). Similarly, the effects of leptin administration in animal models of diet-induced obesity, a model that provides important insights into understanding the effects of leptin on glucose metabolism in obese humans, also reveal largely null data (27,283).…”
Section: Physiological Role Of Leptin In the Regulation Of Insulin Sementioning
confidence: 99%
“…This is despite the presence of markers of leptin resistance, including increased basal SOCS3 mRNA that is measured in DIO rodents that are leptin-resistant [24,25,45,53] and the absence of leptin-stimulated increases in pSTAT3 and SOCS3. While there are notable differences in the manner by which rats and humans respond to a KD, elucidation of the neural and endocrine effects of decreased carbohydrate and chronically elevated ketone bodies provides insight into how dietary macronutrients affect individual systems involved in overall regulation of energy balance.…”
Section: Discussionmentioning
confidence: 99%